(untitled) (The Strategic Review for Southern Africa, 2020)
This paper discusses the Decolonising Knowledge Seminar, a seminar which I initiatedin the Humanities Faculty at the University of the Free State’s (UFS) Bloemfontein campus in 2017. The paper’s opening sections present a rationale for the seminar. I maintain that there is considerable scholarship illuminating how colonialpower shaped the knowledge which academic disciplines generated about Africa during the late 19th and early 20th centuries. Much of it is focused on anthropology, the discipline centred on Europe’s non-Western ‘others’ and implicated in latecolonial government. Despite the influence of this and related critiques globally, with their focus on power-knowledge relationships, such work has not substantially permeated South Africa’s Afrikaans universities. There, humanities disciplineswere largely isolated from global knowledge flows during the apartheid era and continue to emerge from this insular past. The paper then discusses the seminar itself and what I see as its three main contributions: creating space for an open-endedexchange about colonial knowledge and its legacies, engaging critically with the language of decolonisation, and grounding discussion of decolonisation in scholarship on Africa’s colonial history, including the history of anthropology. Bytracing these dynamics, the paper offers a unique perspective on the unfolding conversation about decolonisation in South Africa, highlighting a specific initiative aimed at contributing to decolonising knowledge at one South African university.Moreover, the paper suggests how historical literature pertaining to anthropology speaks to decolonising knowledge at the UFS and Afrikaans universities generally, where questions of colonial knowledge and power have long been obscured. In this manner, the paper moves the topic of decolonisation from highly abstract and/or politically symbolic claims into a specific context, where engaging certain scholarly texts may make a demonstrable intervention.